2014
DOI: 10.1055/s-0033-1340838
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Cyclopropanation Reactions

Abstract: Both physical and organic chemists are interested in the cyclopropane ring, the former owing to the strain inherent to the small ring structure, the latter prompted by the importance of this ring in naturally occurring compounds. In recent years, the increasing interest in enantioselective organic synthesis has led to a large number of papers on the preparation of cyclopropane compounds in enantioenriched form. The last review on asymmetric cyclopropanation reactions is dated 2008, thus an update is necessary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(16 citation statements)
references
References 155 publications
(231 reference statements)
0
16
0
Order By: Relevance
“…Although various optically active cis -cyclopropane derivatives have been synthesized, construction of arylmethylcyclopropane and arylcyclopropane structures, particularly those with the desired heteroaryl group, remains challenging. We are interested in the synthesis and application of these chiral structures as an rigid-core for medicinal chemical studies, and have developed efficient methods for synthesizing chiral di-, tri-, or tetrasubstituted cyclopropanes conjugated with an aryl or a heteroaryl group. …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although various optically active cis -cyclopropane derivatives have been synthesized, construction of arylmethylcyclopropane and arylcyclopropane structures, particularly those with the desired heteroaryl group, remains challenging. We are interested in the synthesis and application of these chiral structures as an rigid-core for medicinal chemical studies, and have developed efficient methods for synthesizing chiral di-, tri-, or tetrasubstituted cyclopropanes conjugated with an aryl or a heteroaryl group. …”
Section: Resultsmentioning
confidence: 99%
“…The residue was purified by silica gel column chromatography (33−50% AcOEt in hexane) to give 3 (7.3 mg, 0.014 mmol, 33% for 2 steps) as a yellow oil. [α] D 23 = +4.6 (c 0.33, CHCl 3 ); 1 H NMR (500 MHz, CDCl 3 ) δ 0.28 ( (9H-Fluoren-9-yl)methyl {(1R,2S)-2-[2-(6,7-dimethylchromon-3yl)ethyl]cyclopropyl}carbamate (37). To a solution of 29 (61 mg, 0.22 mmol) in AcOEt (2.2 mL) was added 10% palladium on carbon (18 mg) at room temperature, and the mixture was stirred at 0 °C for 1 h under an H 2 atmosphere.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
See 1 more Smart Citation
“…FTIR (neat): 3058, 3027, 1666, 1597, 1579, 1513, 1217, 899, 692 cm −1 . 1 6.63 (d, J = 15.9 Hz, 1H), 6.34 (dd, J = 15.9, 9.1 Hz, 1H), 3.32 (dd, J = 9.1, 6.0 Hz, 1H), 3.25 (t, J = 6.0 Hz, 1H), 2.70 (td, J = 9.1 6.0 Hz, 1H). 13…”
Section: (E)-3-(naphthalen-2-yl)-1-phenylprop-2-en-1-one (2o)mentioning
confidence: 99%
“…Cyclopropanation of olefins is of particular interest as it provides access to conformationally constrained and stereochemically rich cyclopropane rings, which represent key building blocks for the discovery and development of drugs and other biologically active molecules [ 14 ]. Copper–Schiff base complexes are of particular significance because they have proven to be effective for the intermolecular cyclopropanation of olefins as well as for intramolecular cyclopropanation; the successful industrial application of these kinds of catalysts makes them a significant achievement in catalysis [ 15 ]. Li et al has pointed out that modifications of the salicylaldehyde moiety to improve the catalysts have not been reported so far; they studied the electronic effects of substituents on the salicylaldehyde framework and found that electron withdrawing groups, such as the nitro group, and electron donating groups, such as the methyl group, can influence the catalytic process [ 16 ].…”
Section: Introductionmentioning
confidence: 99%